DEVELOPMENT OF CULTURAL BEHAVIOR THROUGH NATURE IN PRESCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article explores the impact of influencing nature on the development of cultural behavior in preschool children. Studies existing literature to understand how the natural environment affects various aspects of socialization and cultural education. The review also explores the methodologies used in relevant research, analyzes their results, and provides insight into their impact on early childhood education and environmental policy.